Purification, structural characterization and biotechnological potential of tannase enzyme produced by Enterobacter cloacae strain 41. (February 2019) - R.K., Govindarajan; Krishnamurthy, Mathivanan; Neelamegam, Rameshkumar; Shyu, Douglas J.H.; Muthukalingan, Krishnan; Nagarajan, Kayalvizhi
Graphical abstract: Highlights: Optimization of culture condition of tannase from Enterobacter cloacae . Tannase from E. cloacae was purified and characterized. The molecular weight of purified tannase was ∼45 kDa and its activity was analyzed by zymogram. The purified tannase was analyzed by MALDI-TOF-MS, FT-IR and circular dichroism (CD) and the enzymatic reaction product was analyzed by HPLC. The enzyme is stable over a good range of temperature and pH. Abstract: Tannase production by Enterobacter cloacae strain 41 was investigated under submerged fermentation which was optimized at various circumstances such as pH, temperature, substrate, and agitation, carbon, and nitrogen sources. Tannase was purified by a two-step approach comprising of ion exchange and size exclusion chromatography, respectively. The maximum tannase production was achieved at 1.0% tannic acid concentration, incubation temperature of 50 °C, and initial pH 6.0. The molecular weight of purified tannase was 45 kDa on 10% SDS-PAGE, and it was confirmed by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry (MS). The enzymatic products of purified tannase were characterized by HPLC, TLC and FT-IR spectroscopy which showed the functional groups such as OH, CO, and CC. The purified tannase retained the activity up to 90% under the condition at 50 °C and pH 6.0 after 1 h incubation. Enzyme kinetics and inhibition studies were also investigated. Cytotoxicity studies showed that the tannase has no cytotoxic effects on Vero cell line. The results indicated the E. cloacae strain 41 would give a potential source for the efficient production of tannase and can be used in tannery effluent degradation, food, and pharmaceutical industrial applications.